2015
DOI: 10.1007/s11240-015-0806-3
|View full text |Cite
|
Sign up to set email alerts
|

Alkanna orientalis (L.) Boiss. plant isolated cultures and antimicrobial activity of their extracts: phenomenon, dependence on different factors and effects on some membrane-associated properties of bacteria

Abstract: Herbal medicine requires searching for new sources with antimicrobial activity. Alkanna sp. (Boraginaceae) is widely used in medicine due to detoxification and antibacterial effects. The aim of this study was to obtain Alkanna orientalis (L.) Boiss. plant callus extracts, to investigate antimicrobial activity of extracts against bacteria and yeast and to reveal responsible mechanisms. Callus tissue cultures have been obtained using different nutrient media. Antimicrobial activity and minimal inhibitory concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Mothana and Lindequist [31] showed that methanol extracts were more active than chloroform extracts which confirms our data. In our study aqueous extracts have shown poor antimicrobial activities at tested concentrations which coincides with literature data [3, 10, 31–33]. …”
Section: Results and Dicussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mothana and Lindequist [31] showed that methanol extracts were more active than chloroform extracts which confirms our data. In our study aqueous extracts have shown poor antimicrobial activities at tested concentrations which coincides with literature data [3, 10, 31–33]. …”
Section: Results and Dicussionsupporting
confidence: 92%
“…It is well known that about quarter part of current medications is derived from compounds of plant origin [1, 7]. Plant-derived compounds could have other target sites than traditional antimicrobials and subsequently having different mechanisms of action against microbes [6, 810]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates (2001) reported that quarter part of current medications is derived from compounds of plant origin. Ahmad and Beg (2001); Petrosyan et al;(2015) reported that plant derived compounds could have other target sites than traditional antimicrobials and subsequently having different mechanism of action against microbes. (2010); Rajesh et al;(2010); Cowan (2012); Upadhyaya et al; reported that plant secondary metabolites have different groups such as Phenolics, and poly phenols (flavonoids, quinines, tannins, coumarins,), terpenoids, alkaloids, lectins and polypeptides.…”
mentioning
confidence: 99%
“…We have a long list of medicinal plants but only few have been evaluated in vitro for their antimicrobial activities in vitro (Borris 1996;Petrosyan et al;2015). From the ancient times, people started to use plant materials to treat infectious disease, to heal the cuts and wound without knowing about the causative agents present among the plants.…”
mentioning
confidence: 99%